KELUARGA SAKINAH PERSPEKTIF HADIS (Kajian Hadis Maudhu’í) - tita rosalina (Samawa (Sakinah, Mawaddah Warahmah), 2023)
The family is also the soul and backbone of a country, the physical and spiritual well-being experienced is a reflection of the situation of the family living in the midst of the community itself. Thus, if we want to create baldatun thayyibatun (a good state), the foundation that we must build is a marhamah society, namely the creation of a sakinah family. The pillars that must be upheld to make it happen are faith, mawaddah and mercy. With the figure of a father who is wise, compassionate, gentle and able to educate and raise children with love will shape the child's character to be strong, thus the family is the most important school through a mother's upbringing. This research was made based on a review of several sources of literature review (literature study) or library research that is relevant to the topic discussed, namely the focus on the study of the Sakinah Family including: the understanding or concept of the sakinah family, the characteristics or characteristics of the sakinah family and hadiths hadith about the sakinah family. A sakinah family is a family that is harmonious, happy both physically and mentally, living a calm, peaceful, peaceful life and full of love. The term "sakinah" is used in the Qur'an to describe family comfort. This term has the same root as "sakanun" which means a place to live. So, it is easy to understand if the term is used by the Qur'an to refer to the place where each family member is anchored in a comfortable and calm atmosphere, so that it becomes a fertile ground for the growth of love (mawaddah wa rahmah) among its members. So, the word sakinah which is used to characterize the word "family" is a value system that should be the driving force in building a family order that can provide comfort in the world while at the same time guaranteeing safety in the hereafter. The basis for the sakinah family's law is found in the hadith of the Prophet. sourced from Abu Hurairah r.a. as narrated by Bukhary namely: "Having told us Musaddad. Having told us Yahya from Ubaidullah he said; Has told me Sa'id bin Abu Sa'id from his father from Abu Hurairah ra radliallahu 'anhu, from the Prophet sallallaahu 'alaihi wasallam, he said: "The woman was married for four things, because of her wealth, because of her offspring, because of her beauty and because of her religion. So choose because of his religion, surely you will be lucky.